Structure and Corrosion Behavior of Sputter-Deposited W-Mo Alloys - Bhattarai, Jagadeesh (Journal of Nepal Chemical Society, 2006)
Nanocrystalline, single bcc solid solutions of W-Mo alloys have been successfully prepared by D. C. magnetron sputtering in a wide composition. The corrosion behavior of the sputter-deposited W-Mo alloys was studied. The W-Mo alloys showed significantly high corrosion resistance in 12 M HCl at 30o C. Their corrosion rates are about one and half orders of magnitude lower than that of sputter-deposited tungsten and lower than that of the sputter-deposited molybdenum even after prolonged immersion. DOI: 10.3126/jncs.v21i0.217 Journal of Nepal Chemical Society Vol.21 2006 pp.19-25